(untitled) (Prilozi za orijentalnu filologiju, 2017)
Ali-Fehmi Džabić (1853-1918) is undoubtedly one of the most prominent figures among our authors writing in the Arabic language. His commentary in the field of the classical Arabic poetıy present him as one of literary critics who, although far away from their homeland and their mother tongue, managed to master this field to such an extent that they aroused the admiration and respect of ali connoisseurs of this field. There are a number of works devoted to Ali-Fehmi Džabić and his acti- vities; hovvever, they mainly treat his political activities as the leader of the movement of Muslims in Bosnia and Herzegovina for religious and waqf- -mcfârif autonomy. It was in this capacity that he left for İstanbul, which the National Government used to proclaim him an unauthorised emigrant, pre- venting him from returning to his homeland ever. His departure for Istanbul marks a new period in the work of Ali-Fehmi Džabić as a professor of the Arabic language and literature and as an antho- logist and literary critic specialised in the classical Arabic poetry. This paper discusses his work entitled Tılbat af-talih fi sarp Lâmiyya Abî Talih a com- mentary on Abü Tâlib’s religious poem Lâmiyya.